Genomic Characterization and Hydrolysis Enzyme of Piscibacillus salipiscarius RBU1-1ᵀ and Allobacillus salarius SKP4-8ᵀ Isolated from Fermented Fish Products - Namwong, Sirilak; Chaimongkol, Apichai; Kingkaew, Engkarat; Phongsopitanun, Wongsakorn; Chamroensaksri, Nitcha; Tanasupawat, Somboon (My University, 2026)
Two halophilic bacterial strains, Piscibacillus salipiscarius RBU1-1ᵀ and Allobacillus salarius SKP4-8ᵀ, were isolated from traditional Thai fermented foods, namely pla-ra from Ratchaburi, Thailand, and ka-pi from Samut Sakhon, Thailand, respectively. Comparative genomics confirmed their taxonomic distinctiveness, with RBU1-1ᵀ representing a novel species and SKP4-8ᵀ showing clear genomic separation from its closest relatives. The draft genomes were 2.99 Mb (36.7 mol% G+C) for RBU1-1ᵀ and 2.59 Mb (38.8 mol% G+C) for SKP4-8ᵀ. Both strains encoded hydrolytic enzymes and secondary metabolite pathways, with SKP4-8ᵀ displaying higher protease activity and RBU1-1ᵀ harboring ectoine biosynthetic and stress-response genes. RBU1-1ᵀ encoded the biosynthesis pathways for ectoine, tryptophan, and thiamine, while SKP4-8ᵀ encoded thiamine, riboflavin, coenzyme A, and menaquinone, indicating their potential contributions to postbiotic and nutritional value. Safety assessment revealed the absence of biogenic amine, antibiotic biosynthesis, and major virulence genes in both strains. Although antimicrobial resistance-associated genes were detected, no complete clusters were identified, suggesting low phenotypic risk. Computational pathogenicity prediction indicated a low probability for RBU1-1ᵀ (0.242) and a higher probability for SKP4-8ᵀ (0.945), though these require cautious interpretation. Overall, genomic evidence and enzymatic activity support RBU1-1ᵀ and SKP4-8ᵀ as safe, functional starter culture candidates, with RBU1-1ᵀ showing strong potential through postbiotic biosynthesis and SKP4-8ᵀ through proteolytic activity.
Keywords: Allobacillus salarius; Fermented fish product; Halophilic bacteria; Piscibacillus salipiscarius